Research on the Train Surface Pressure Characteristics in Passing through Tunnels at Speeds of 400 km/h and above - HU Yingcan; DU Jian; CAI Junshuang; HU Chong; LU Yibin (Chengshi guidao jiaotong yanjiu)
［Objective］ In order to ensure the running safety of trains with a speed of 400 km/h and above when passing through tunnels and improve the passenger ride comfort, it is necessary to adopt the numerical simulation method to study the characteristics of the pressure on the train body surface when passing through tunnels. ［Method］ The one-dimensional flow theory and the method of characteristic lines of generalized Riemann variables are introduced and verified through dynamic model tests. The influence patterns of different train running speeds and different tunnel lengths on the train body surface pressure when an 8-car marshalling train passes through the tunnel are explored, and the distribution characteristics of surface pressure on different vehicle bodies are analyzed. ［Result & Conclusion］ When the train running speed is 400 km/h and the tunnel length is 0.7 km, the maximum positive pressure value, the maximum pressure amplitude, and the maximum negative pressure value on the train surface all reach their peak values. When the tunnel length exceeds 0.7 km, the maximum positive pressure value basically does not change with the increase of tunnel length, while the maximum negative pressure value and the maximum pressure amplitude gradually decrease as the tunnel length increases. With different train running speeds, the pressure values on the train surface gradually increase with the increase of train running speed. For the same train running at a speed of 400 km/h, the different parts of the train in descending order of the maximum positive pressure value and the maximum pressure amplitude on their surfaces are the head car, the intermediate car, and the end car, while in ascending order of the maximum negative pressure are the head car, the intermediate car, the end car. Numerically, the maximum positive pressure value, the maximum negative pressure value, and the pressure amplitude on the train body surface all gradually decrease as the distance of the measuring points from the nose tip of the train head increases.